A kind of water-based high solid content conductive agent and preparation method thereof

By using sulfur-doped carbon nanotubes and modified carbon black, combined with dispersant, the problem of carbon nanotube agglomeration in the conductive agent of lithium-ion batteries is solved, the conductive performance and solid content are improved, and the electrochemical performance of lithium-ion batteries is improved. and processing convenience.

CN116706066BActive Publication Date: 2024-12-27SHENZHEN JINBAINA NANO TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310634981.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-31
Publication Date
2024-12-27
Estimated Expiration
2043-05-31

AI Technical Summary

Technical Problem

Carbon nanotubes in the conductive agents of existing lithium-ion batteries are prone to agglomeration, resulting in limited addition, reducing the conductive properties and solid content, and affecting battery performance.

Method used

The dispersion and conductivity of sulfur-doped carbon nanotubes and modified carbon black are improved by ultrasonic dispersion and high-temperature calcination, and the dispersion of carbon black is increased by oxygen plasma modification treatment. Combine an appropriate amount of dispersant to improve the dispersion of the conductive material in the aqueous conductive agent.

Benefits of technology

It significantly improves the solid content and conductivity of the conductive agent, improves the electrochemical performance of lithium-ion batteries, and reduces the viscosity of the conductive agent, making it easier to process and assembly afterwards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004259874470000081
    Figure BDA0004259874470000081
  • Figure BDA0004259874470000091
    Figure BDA0004259874470000091
Patent Text Reader

Abstract

The present application relates to the field of conductive agents, and specifically discloses a water-based high-solid conductive agent and a preparation method thereof. The raw materials used for the conductive agent include the following components in parts by weight: 15-25 parts of sulfur-doped carbon nanotubes, 5-7 parts of carbon black, 1-5 parts of dispersant, and 79-89 parts of water; its preparation method is: adding the dispersant to water and stirring and dispersing for 60min-90min, then adding sulfur-doped carbon nanotubes and carbon black, continuing to stir and disperse for 90min-120min, then grinding for 10h-15h, sieving, cooling, and obtaining a conductive agent. The water-based conductive agent of the present application has a high solid content and a low viscosity, which is convenient for the subsequent processing of negative electrode slurry and the assembly of lithium-ion batteries, and has strong conductivity, which can significantly improve the electrochemical performance of lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of conductive agents, and more specifically, to an aqueous high-solid conductive agent and a preparation method thereof. Background Art

[0002] With the rapid development of society, environmental degradation and energy shortage are two major problems facing mankind, and the main cause of these two problems is the burning of large amounts of fossil fuels. In order to reduce dependence on fossil fuels, it is necessary to vigorously develop new energy sources such as wind, light, and electricity to replace high-energy-consuming and high-polluting traditional energy sources. Among them, lithium-ion batteries with high energy density, long cycle life, and strong safety performance are gradually gaining favor. Especially in recent years, with the popularity of electric vehicles and smart phones, the lithium-ion battery industry has ushered in a golden period of rapid development.

[0003] The negative electrode slurry of lithium-ion batteries mainly includes active materials, binders, conductive agents and solvents. Among them, the conductive agent is an important factor affecting the performance of lithium-ion batteries. The conductive material in the conductive agent is mostly carbon black, but because the carbon black and the active material are in point-to-point contact, the contact surface is small and the conductivity is poor. Therefore, carbon nanotubes and carbon black are usually used in combination at present. The one-dimensional linear structure of carbon nanotubes and the zero-dimensional structure of carbon black are combined to form a point-to-line contact network structure, which increases the contact area between the conductive material and the active material and improves the conductivity of the conductive material.

[0004] However, since the role of the conductive agent in lithium-ion batteries is to provide a channel for electron movement, it does not provide capacity itself, which makes it unsuitable to add too much conductive agent to the negative electrode slurry. If the amount added is too much, the relative content of active materials in the negative electrode slurry will be reduced, thereby affecting the capacity of the lithium-ion battery. At present, in order to enable the conductive agent to play an excellent conductive performance in lithium-ion batteries at a lower addition amount, the method of increasing the content of conductive materials in the conductive agent is usually adopted, that is, increasing the solid content of the conductive agent. However, due to the strong electrostatic force and van der Waals force between the surface molecules and atoms of carbon nanotubes, it is easy to agglomerate and entangle, and it is easy to aggregate in the conductive agent and difficult to disperse, which greatly limits the addition of carbon nanotubes, thereby reducing the solid content of the conductive agent, and then reducing the conductive performance of the conductive agent. Summary of the invention

[0005] In order to solve the above problems, the present application provides an aqueous high-solid content conductive agent and a preparation method thereof.

[0006] In the first aspect, the present application provides an aqueous high solid content conductive agent, which adopts the following technical solution:

[0007] A water-based high-solid conductive agent, the raw materials used include the following components:

[0008] 15-25 parts by weight of carbon nanotubes;

[0009] Carbon black 5-7 parts by weight;

[0010] Dispersant 1-5 parts by weight;

[0011] Water 79-89 parts by weight;

[0012] The carbon nanotubes are sulfur-doped carbon nanotubes.

[0013] By adopting the above technical solution, the electronic structure of the surface of sulfur-doped carbon nanotubes changes due to the incorporation of sulfur atoms, and the Fermi level also changes accordingly, the surface inertness is activated, it is not easy to agglomerate, and it can be better dispersed in the conductive agent. Therefore, the conductive agent of the present application uses sulfur-doped carbon nanotubes instead of ordinary carbon nanotubes, which can greatly increase the usage of sulfur-doped carbon nanotubes, thereby improving the conductive properties of the conductive agent, and then improving the electrochemical properties of lithium-ion batteries. In addition, the amount of carbon black used in the present application is relatively low, so that the viscosity of the conductive agent of the present application can still be maintained at a relatively low level, which is convenient for the subsequent processing of the negative electrode slurry and the assembly of lithium-ion batteries.

[0014] In addition, the conductive agent of the present application is a water-based conductive agent. The hydrophobic properties of the surface of ordinary carbon nanotubes make it difficult to disperse in aqueous solvents, while the incorporation of sulfur atoms greatly improves the hydrophobic properties of carbon nanotubes. The hydrophilic functional groups (C-SO x ), so that the sulfur-doped carbon nanotubes have strong hydrophilic properties and can be better dispersed in aqueous solvents, greatly increasing the amount of sulfur-doped carbon nanotubes added in the aqueous conductive agent.

[0015] Preferably, the sulfur-doped carbon nanotubes are prepared by the following method:

[0016] The carbon nanotubes are added to a magnesium sulfate solution, ultrasonically dispersed for 2h-2.5h, then dried at 70°C-80°C for 48h-60h, then heated to 800°C-850°C, kept warm for 60min-70min, then cooled to room temperature, acid-washed, and purified to obtain sulfur-doped carbon nanotubes; wherein the mass volume ratio of the carbon nanotubes to the magnesium sulfate solution is 0.08g / ml-0.1g / ml.

[0017] By adopting the above technical solution, the carbon nanotubes of the present application are multi-walled carbon nanotubes. The present application uses multi-walled carbon nanotubes as the initial raw material and magnesium sulfate as the sulfur source. By using a high-temperature calcination method, sulfur atoms are embedded in the skeleton of the carbon material and connected to the carbon atoms in a covalent bond manner, thereby increasing the pore volume and specific surface area of ​​the sulfur-doped carbon nanotubes, thereby increasing the conductivity of the sulfur-doped carbon nanotubes. At the same time, the hydrophilic functional group C-SO formed by the combination of sulfur atoms and carbon atoms x , making the sulfur-doped carbon nanotubes show better hydrophilicity. In addition, the acid washing process in the method for preparing sulfur-doped carbon nanotubes of the present application can remove Mg to a great extent, reducing the possibility that the Mg content affects the properties of the sulfur-doped carbon nanotubes.

[0018] Preferably, the mass fraction of the magnesium sulfate solution is 20%-30%.

[0019] Preferably, the diameter of the carbon nanotubes is 20nm-50nm.

[0020] By adopting the above technical solution, the present application uses carbon nanotubes with larger diameters, which can reduce the viscosity of the conductive agent and facilitate the subsequent processing of the negative electrode slurry and the assembly of the lithium-ion battery.

[0021] Preferably, the carbon black is modified by oxygen plasma.

[0022] By adopting the above-mentioned technical scheme, the present application places carbon black into a plasma treatment instrument, introduces oxygen into it, and uses oxygen plasma to perform surface modification treatment on the carbon black. A variety of oxygen-containing functional groups can be introduced on the surface of the carbon black, thereby increasing the polarity of the carbon black surface, thereby improving the dispersibility of the carbon black in the aqueous conductive agent.

[0023] Preferably, the oxygen plasma modification treatment has a processing power of 50W-80W, a processing time of 3min-5min, and a processing pressure of 20Pa-30Pa.

[0024] By adopting the above technical solution, the present application controls the processing power, processing time and processing pressure, and can increase the number of active particles that play a surface modification role in the plasma atmosphere, thereby improving the modification effect of carbon black. However, when the processing power, processing time and processing pressure reach a certain value, the generation and deactivation of active particles have tended to balance, and the processing effect has reached the most significant. Further increase will reduce the processing effect.

[0025] Preferably, the dispersant is one or more of polyvinyl pyrrolidone, cationic dispersant KD1 and non-ionic dispersant BYK-2150.

[0026] By adopting the above technical scheme, the present application adopts one of polyvinyl pyrrolidone, cationic dispersant KD1 and non-ionic dispersant BYK-2150 or adopts multiple of them in any proportion to add to the conductive agent, which can reduce the possibility of agglomeration of the conductive material in the conductive agent, thereby making the conductive material well and stably dispersed in the conductive agent.

[0027] Preferably, the dispersant is a cationic dispersant KD1 and a nonionic dispersant BYK-2150, and the weight ratio of the cationic dispersant KD1 to the nonionic dispersant BYK-2150 is 1:(0.8-1.2).

[0028] By adopting the above technical solution, the present application further adopts a mixed use of cationic dispersant KD1 and non-ionic dispersant BYK-2150, and by controlling the weight ratio of the two, the synergistic effect of the two is fully exerted, thereby further improving the dispersibility of the conductive material in the conductive agent.

[0029] In a second aspect, the present application provides a method for preparing an aqueous high solid content conductive agent, comprising the following steps:

[0030] Add the dispersant into water, stir and disperse for 60min-90min at a speed of 1000r / min-1800r / min, then add sulfur-doped carbon nanotubes and carbon black, continue to stir and disperse for 90min-120min, then grind at a speed of 1000r / min-1200r / min for 10h-15h, sieve, cool, and obtain a conductive agent.

[0031] By adopting the above technical solution, the present application first mixes the dispersant with water, then adds sulfur-doped carbon nanotubes and carbon black, so that the sulfur-doped carbon nanotubes and carbon black are fully dispersed in the aqueous solvent, and then grinds and filters through a 150-200 mesh sieve, and obtains the conductive agent after cooling. The preparation method of the present application is simple in steps, easy to operate, and suitable for large-scale industrial production.

[0032] Preferably, the carbon black is ball-milled for 96h-168h before being added.

[0033] By adopting the above technical solution, the present application puts the carbon black into a ball mill for ball milling before adding it to the conductive agent. The grinding medium in the ball mill moves violently under the action of centrifugal force, and disperses the secondary agglomerated carbon black into primary particles with high-intensity mechanical force, thereby improving the dispersibility of carbon black in the aqueous conductive agent. Furthermore, the present application uses zirconia beads with a ball diameter of 3mm-10mm as grinding media during the ball milling process. The present application enhances the ball milling effect of carbon black by controlling the particle size of the grinding medium. Furthermore, the weight ratio of zirconia beads with a ball diameter of 8mm-10mm, zirconia beads with a ball diameter of 5mm-8mm, and zirconia beads with a ball diameter of 3mm-5mm is 1:1:2. The grinding medium under this ratio has a better ball milling effect on carbon black, and the dispersion effect of carbon black after ball milling is better.

[0034] In summary, this application has the following beneficial technical effects:

[0035] 1. The sulfur-doped carbon nanotubes and carbon black of the present application have strong dispersibility, the solid content of the aqueous conductive agent is high, and the conductive performance is strong, which can significantly improve the electrochemical performance of lithium-ion batteries;

[0036] 2. The amount of sulfur-doped carbon nanotubes added to the aqueous conductive agent is relatively high, reaching more than 22.5%;

[0037] 3. The amount of carbon black added in the present application is relatively small, and can reach a minimum of 4.0%. The viscosity of the conductive agent is relatively low, which facilitates the subsequent processing of the negative electrode slurry and the assembly of the lithium-ion battery. DETAILED DESCRIPTION

[0038] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.

[0039] Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically:

[0040] Multi-walled carbon nanotubes were purchased from Guangzhou Hongwu Material Technology Co., Ltd.

[0041] Carbon black, purchased from Shandong Xuanhao Environmental Protection Technology Co., Ltd., model N330;

[0042] Polyvinyl pyrrolidone was purchased from Jinan Haokun Chemical Co., Ltd.

[0043] Cationic dispersant KD1, produced by Croda Technology;

[0044] Non-ionic dispersant BYK-2150, produced by BYK in Germany.

[0045] <Preparation Example>

[0046] Preparation Example 1

[0047] The preparation method of sulfur-doped carbon nanotubes is as follows:

[0048] First, 40g of multi-walled carbon nanotubes (tube diameter is 20nm-50nm) are added to 500ml of 20% magnesium sulfate solution by mass, and ultrasonically dispersed in an ultrasonic crusher for 2h, then placed in an oven, dried at 70°C for 48h, and then heated to 800°C in a horizontal tube furnace, kept warm for 60min, and then cooled to room temperature. The obtained product is taken out, and after acid washing and purification, sulfur-doped carbon nanotubes are obtained.

[0049] Preparation Example 2

[0050] The preparation method of sulfur-doped carbon nanotubes is as follows:

[0051] First, 45g of multi-walled carbon nanotubes (tube diameter is 20nm-50nm) are added to 500ml of 25% magnesium sulfate solution, and ultrasonically dispersed in an ultrasonic crusher for 2.2h, then placed in an oven, dried at 75°C for 54h, and then heated to 830°C in a horizontal tube furnace, kept warm for 65min, and then cooled to room temperature. The obtained product is taken out, acid-washed, and purified to obtain sulfur-doped carbon nanotubes.

[0052] Preparation Example 3

[0053] The preparation method of sulfur-doped carbon nanotubes is as follows:

[0054] First, 50g of multi-walled carbon nanotubes (tube diameter is 20nm-50nm) are added to 500ml of 30% magnesium sulfate solution by mass, and ultrasonically dispersed in an ultrasonic crusher for 2.5h, then placed in an oven, dried at 80°C for 60h, and then heated to 850°C in a horizontal tube furnace, kept warm for 70min, and then cooled to room temperature. The obtained product is taken out, and after acid washing and purification, sulfur-doped carbon nanotubes are obtained.

[0055] <Example>

[0056] Examples 1.1-1.5

[0057] A method for preparing an aqueous high-solid content conductive agent comprises the following steps:

[0058] The dispersant (polyvinyl pyrrolidone) was added into water, and the mixture was stirred and dispersed for 90 minutes at a speed of 1000 r / min. Then, the sulfur-doped carbon nanotubes and carbon black prepared in Preparation Example 1 were added, and the mixture was stirred and dispersed for 90 minutes. The mixture was then ground at a speed of 1200 r / min for 10 hours, filtered through a 150-mesh sieve, and cooled to obtain a conductive agent.

[0059] Table 1 Amount of each raw material used in Examples 1.1-1.5 Unit: g

[0060] project Polyvinylpyrrolidone water Sulfur-doped carbon nanotubes Carbon Black Example 1.1 5 89 15 7 Example 1.2 1 79 25 5 Example 1.3 3 84 20 6 Example 1.4 5 89 25 5 Example 1.5 1 79 15 7

[0061] Example 1.6

[0062] A method for preparing an aqueous high-solid content conductive agent comprises the following steps:

[0063] Add 1 g of dispersant (cationic dispersant KD1) to 79 g of water, stir and disperse at a speed of 1400 r / min for 75 min, then add 25 g of sulfur-doped carbon nanotubes obtained in Preparation Example 2 and 5 g of carbon black, continue stirring and dispersing for 105 min, and then grind at a speed of 1100 r / min for 12.5 h, filter through a 200-mesh sieve, and cool to obtain a conductive agent.

[0064] Example 1.7

[0065] A method for preparing an aqueous high-solid content conductive agent comprises the following steps:

[0066] Add 1 g of dispersant (non-ionic dispersant BYK-2150) to 79 g of water, stir and disperse at a speed of 1800 r / min for 60 min, then add 25 g of sulfur-doped carbon nanotubes obtained in Preparation Example 3 and 5 g of carbon black, continue stirring and dispersing for 120 min, and then grind at a speed of 1000 r / min for 15 h, filter through a 150-mesh sieve, and cool to obtain a conductive agent.

[0067] Examples 2.1-2.2

[0068] A method for preparing an aqueous high-solid conductive agent, which differs from Example 1.2 in that: in the method for preparing sulfur-doped carbon nanotubes, the diameter of the carbon nanotubes is selected in a different range, and the rest is the same as Example 1.2; wherein, the diameter of the carbon nanotubes in Example 2.1 is 8nm-15nm; and the diameter of the carbon nanotubes in Example 2.2 is 15nm-20nm.

[0069] Examples 3.1-3.5

[0070] A method for preparing an aqueous high-solid conductive agent, which is different from Example 1.2 in that the carbon black is subjected to oxygen plasma modification treatment, and the rest is the same as Example 1.2; the specific process is as follows:

[0071] The carbon black was placed in a plasma treatment apparatus, evacuated to 10 Pa, and after oxygen washing 2-3 times, oxygen was introduced for modification treatment; the treatment conditions of Examples 3.1-3.5 are shown in Table 2.

[0072] Table 2 Treatment conditions of oxygen plasma modification treatment

[0073] project Processing power W Processing time min Processing pressure Pa Example 3.1 50 5 20 Example 3.2 80 3 30 Example 3.3 100 3 30 Example 3.4 80 10 30 Example 3.5 80 3 60

[0074] Examples 4.1.1-4.1.4

[0075] A method for preparing an aqueous high-solid conductive agent, which is different from Example 1.2 in that: the dispersant is a mixture of a cationic dispersant KD1 and a non-ionic dispersant BYK-2150 in a weight ratio of 1:(0.8-1.2), wherein the specific amount of the dispersant in Examples 4.1.1-4.1.4 is shown in Table 3.

[0076] Table 3 Specific dosage of dispersant Unit: g

[0077] project Cationic dispersant KD1 Nonionic dispersant BYK-2150 Example 4.1.1 0.56 0.44 Example 4.1.2 0.45 0.55 Example 4.1.3 0.67 0.33 Example 4.1.4 0.4 0.6

[0078] Example 4.2.1

[0079] A method for preparing an aqueous high-solid conductive agent, which differs from Example 1.2 in that: a dispersant is a mixture of a cationic dispersant KD1 and polyvinyl pyrrolidone in a weight ratio of 1:0.8, wherein the cationic dispersant KD1 is 0.56 g and the polyvinyl pyrrolidone is 0.44 g.

[0080] Example 4.2.2

[0081] A method for preparing an aqueous high-solid content conductive agent, which is different from Example 1.2 in that: the dispersant is a mixture of polyvinyl pyrrolidone and a non-ionic dispersant BYK-2150 in a weight ratio of 1:0.8, wherein the polyvinyl pyrrolidone is 0.56g and the non-ionic dispersant BYK-2150 is 0.44g.

[0082] Example 5.1

[0083] A method for preparing a water-based high-solid content conductive agent, which is different from Example 1.2 in that the carbon black is ball-milled before being added, and the rest is the same as Example 1.2; the specific process is as follows:

[0084] Put carbon black into a ball mill, then add 5g of zirconia beads with a ball diameter of 3mm-10mm and 1ml of ethanol, and ball mill for 96h. Among them, the zirconia beads with a ball diameter of 8mm-10mm are 1.25g, the zirconia beads with a ball diameter of 5mm-8mm are 1.25g, and the zirconia beads with a ball diameter of 3mm-5mm are 2.5g.

[0085] Example 5.2

[0086] A method for preparing a water-based high-solid content conductive agent, which is different from Example 1.2 in that the carbon black is ball-milled before being added, and the rest is the same as Example 1.2; the specific process is as follows:

[0087] Put carbon black into a ball mill, then add 5g of zirconia beads with a ball diameter of 3mm-10mm and 1ml of ethanol, and ball mill for 168h. Among them, the zirconia beads with a ball diameter of 8mm-10mm are 1.25g, the zirconia beads with a ball diameter of 5mm-8mm are 1.25g, and the zirconia beads with a ball diameter of 3mm-5mm are 2.5g.

[0088] Example 6.1

[0089] A method for preparing an aqueous high-solid conductive agent, which is different from Example 5.2 in that: 1.43g of zirconia beads with a ball diameter of 8mm-10mm, 0.71g of zirconia beads with a ball diameter of 5mm-8mm, and 2.86g of zirconia beads with a ball diameter of 3mm-5mm.

[0090] Example 6.2

[0091] A method for preparing an aqueous high-solid conductive agent, which is different from Example 5.2 in that: 1.61 g of zirconia beads with a ball diameter of 8 mm-10 mm, 0.16 g of zirconia beads with a ball diameter of 5 mm-8 mm, and 3.23 g of zirconia beads with a ball diameter of 3 mm-5 mm.

[0092] <Comparative Example>

[0093] Comparative Example 1

[0094] The difference from Example 1.2 is that ordinary carbon nanotubes are used instead of sulfur-doped carbon nanotubes, and the rest is the same as Example 1.2.

[0095] Comparative Example 2

[0096] The difference from Example 1.2 is that nitrogen-doped carbon nanotubes are used instead of sulfur-doped carbon nanotubes. The rest is the same as Example 1.2, wherein the nitrogen-doped carbon nanotubes are purchased from Angxing New Carbon Materials Changzhou Co., Ltd.

[0097] Comparative Example 3

[0098] The difference from Example 1.2 is that ordinary carbon nanotubes are used instead of sulfur-doped carbon nanotubes, the amount of carbon nanotubes added is reduced, and the amount of carbon black used is increased, specifically, 10 g of carbon nanotubes and 20 g of carbon black.

[0099] Comparative Example 4

[0100] The difference from Example 1.2 is that ordinary carbon nanotubes are used instead of sulfur-doped carbon nanotubes, the amount of carbon nanotubes added is reduced, and the amount of carbon black used is increased, specifically, 15g of carbon nanotubes and 15g of carbon black.

[0101] <Performance Testing>

[0102] 1. Solid content: Determine with reference to 5.2 of GB / T 33818-2017. Place heated, dried and cooled glass fiber paper on a dry glass dish, evenly apply the conductive agent prepared in Example 1 on the glass fiber paper, and weigh it. Then put it in a constant temperature drying oven at 130°C for 5 hours, cool it and weigh it again. Repeat this operation until constant weight is reached, and calculate the solid content using the solid content calculation formula.

[0103] 2. Viscosity: Referring to the rotational viscometer method in GB / T 22235-2008, a digital rotational viscometer was used to directly measure the viscosity of the conductive agents prepared in Examples 1-6 and Comparative Examples 1-4. The results are shown in Table 4.

[0104] 3. Electrochemical performance of lithium battery: The conductive agent prepared in Examples 1-6 and Comparative Examples 1-4 was used to prepare graphite material system negative electrode sheets, and LiFePO4 was used as the positive electrode to prepare a battery. The first charge and discharge test was carried out using the Xinwei test system at room temperature with a voltage range of 2.75-4.2V and a current of 0.1C (1C=180mA / g), and then cycled for 100 weeks at 1C. The results are shown in Table 4.

[0105] Table 4 Performance test results

[0106]

[0107]

[0108] After testing, the solid content of the conductive agent prepared in Example 1 is 22.5%-28.2%, and it can be seen from Table 1 that the viscosity of the conductive agent prepared in Example 1 of the present application is below 1000mPa·s, the first week charge and discharge specific capacity is above 180mAh / g, and the capacity retention rate of 1C cycle 100 weeks is above 95%, indicating that the aqueous conductive agent of the present application has a high solid content, and the amount of sulfur-doped carbon nanotubes added to the aqueous conductive agent is high (12.93%-22.73%), the amount of carbon black added is small (4.55%-6.03%), the conductive performance is strong, the prepared lithium ion battery has a high discharge specific capacity and good cycle performance.

[0109] The viscosity of the conductive agent prepared in Example 2 is greater than that in Example 1.2, and the first-week charge-discharge specific capacity and the 1C cycle 100-week capacity retention rate are lower than those in Example 1.2, indicating that the present application further controls the diameter of the carbon nanotubes to reduce the viscosity of the conductive agent.

[0110] The viscosity of the conductive agent prepared in Examples 3.1-3.2 is lower than that in Example 1.2, and the first-week charge-discharge specific capacity and the capacity retention rate after 100 cycles at 1C are higher than those in Example 1.2, indicating that the oxygen plasma modification treatment of carbon black in the present application can improve the dispersibility of carbon black in the conductive agent, thereby improving the conductive properties of the conductive agent.

[0111] The viscosity of the conductive agent prepared in Examples 3.3-3.5 is lower than that in Example 1.2, but higher than that in Examples 3.1-3.2. The first-week charge-discharge specific capacity and the capacity retention rate after 100 cycles at 1C are higher than those in Example 1.2, but lower than those in Examples 3.1-3.2. This indicates that the present application further controls the treatment conditions of the oxygen plasma modification treatment, which can further improve the dispersibility of carbon black in the conductive agent, thereby improving the conductive properties of the conductive agent.

[0112] The viscosity of the conductive agent prepared in Examples 4.1.1-4.1.2 is lower than that in Example 1.2, and the first-week charge-discharge specific capacity and the 1C cycle 100-week capacity retention rate are higher than those in Example 1.2, indicating that the present application adopts a mixed use of cationic dispersant KD1 and non-ionic dispersant BYK-2150, which can further improve the dispersion degree of the conductive material in the conductive agent, thereby improving the conductive properties of the conductive agent.

[0113] The viscosity of the conductive agent prepared in Examples 4.1.3-4.1.4 is lower than that in Example 1.2, but higher than that in Examples 4.1.1-4.1.2. The first-week charge-discharge specific capacity and the capacity retention rate after 100 cycles at 1C are higher than those in Example 1.2, but lower than those in Examples 4.1.1-4.1.2. This indicates that the present application further controls the weight ratio of the cationic dispersant KD1 and the non-ionic dispersant BYK-2150, which can further improve the dispersibility of the conductive material in the conductive agent, thereby improving the conductive properties of the conductive agent.

[0114] The viscosity of the conductive agent prepared in Example 4.2 is lower than that in Example 1.2, but higher than that in Example 4.1. The first-week charge-discharge specific capacity and the capacity retention rate after 100 cycles at 1C are higher than those in Example 1.2, but lower than those in Example 4.1, indicating that the present application gives full play to the synergistic effect between the cationic dispersant KD1 and the non-ionic dispersant BYK-2150, thereby improving the dispersion of the conductive material in the conductive agent.

[0115] The viscosity of the conductive agent prepared in Example 5 is lower than that in Example 1.2, and the first-week charge-discharge specific capacity and the 1C cycle 100-week capacity retention rate are higher than those in Example 1.2, indicating that the ball milling treatment of carbon black in the present application can improve the dispersion of carbon black in the conductive material, thereby further improving the conductive properties of the conductive agent.

[0116] The viscosity of the conductive agent prepared in Example 6 is greater than that in Example 5, and the first-week charge and discharge specific capacity and the 1C cycle 100-week capacity retention rate are lower than those in Example 5, indicating that the present application further controls the weight ratio of zirconia beads with different ball diameters, which can further improve the ball milling effect of carbon black, thereby further improving the dispersibility of carbon black in the conductive material.

[0117] The viscosity of the conductive agent prepared in Comparative Example 1 is greater than that of Example 1.2, and the first-week charge-discharge specific capacity and the 1C cycle 100-week capacity retention rate are lower than those of Example 1.2, indicating that ordinary carbon nanotubes have extremely poor dispersibility in aqueous solvents. When they are added to the conductive agent in the amount used in this application, the carbon nanotubes will agglomerate in large quantities, thereby increasing the viscosity of the conductive agent and reducing the conductive properties of the conductive material.

[0118] The viscosity of the conductive agent prepared in Comparative Example 2 is greater than that of Example 1.2, and the first-week charge and discharge specific capacity and the capacity retention rate after 100 cycles at 1C are lower than those of Example 1.2, indicating that sulfur-doped carbon nanotubes can further improve the dispersibility of carbon nanotubes in the conductive agent compared with nitrogen-doped carbon nanotubes.

[0119] The viscosity of the conductive agent prepared in Comparative Examples 3-4 is significantly greater than that in Example 1.2, and the first-week charge-discharge specific capacity and the 1C cycle 100-week capacity retention rate are slightly lower than those in Example 1.2, indicating that increasing the amount of carbon black used will significantly increase the viscosity of the conductive agent. When the viscosity of the conductive agent is too large, the conductive material is not easy to disperse in the conductive agent, thereby reducing the conductive properties of the conductive agent.

[0120] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A water-based high-solid conductive agent, characterized in that: The raw materials used include the following components: 15-25 parts by weight of carbon nanotubes; Carbon black 5-7 parts by weight; Dispersant 1-5 parts by weight; Water 79-89 parts by weight; The carbon nanotubes are sulfur-doped carbon nanotubes; The sulfur-doped carbon nanotubes are prepared by the following method: The carbon nanotubes are added to a magnesium sulfate solution with a mass fraction of 20%-30%, ultrasonically dispersed for 2h-2.5h, then dried at a temperature of 70°C-80°C for 48h-60h, then heated to 800°C-850°C, kept warm for 60min-70min, then cooled to room temperature, acid-washed, and purified to obtain sulfur-doped carbon nanotubes with a diameter of 20nm-50nm; wherein the mass volume ratio of the carbon nanotubes to the magnesium sulfate solution is 0.08g / ml-0.1g / ml; The carbon black is modified by oxygen plasma; the treatment power of the oxygen plasma modification treatment is 50W-80W, the treatment time is 3min-5min, and the treatment pressure is 20Pa-30Pa; The dispersant is a cationic dispersant KD1 and a nonionic dispersant BYK-2150, and the weight ratio of the cationic dispersant KD1 to the nonionic dispersant BYK-2150 is 1:(0.8-1.2); The preparation method of the aqueous high solid content conductive agent is: Add the dispersant into water, stir and disperse it at a speed of 1000r / min-1800r / min for 60min-90min, then add the sulfur-doped carbon nanotubes and carbon black. Before adding the carbon black, ball mill it for 96h-168h, continue to stir and disperse it for 90min-120min, and then grind it at a speed of 1000r / min-1200r / min for 10h-15h, sieve it, and cool it to obtain the conductive agent.

Citation Information

Patent Citations

  • Carbon nano tube dispersion liquid and preparation method thereof

    CN103700823A

  • Carbon nanotube-graphene composite electric conduction slurry and preparation method and application thereof

    CN104766645A

  • Lithium manganate battery positive electrode piece and preparation method thereof

    CN110718680A